Kampung Hijau: Bonding and Bridging Social Capital in Developing Sustainable Local Tourism - Mutiani, Mutiani; Supriatna, Nana; Abbas, Ersis Warmansyah; Wiyanarti, Erlina; Jumriani, Jumriani (Komunitas, 2022)
Social capital can strengthen social potential in developing various aspects, including local tourism. Regarding the development of local tourism, social capital is described through 2 dimensions: bonds, and bridges (association). Bonding social capital is understood as close kinship capital (family environment to peers). Bridging social capital (association) is described as the capital of relatively distant kinship (coworkers and colleagues). This article describes the relationship between social capital, bonds, and bridges related to local tourism development. The research was conducted in Kampung Hijau Banjarmasin. The results show that the social capital of bonds and bridges, rooted in religious values and inherited through family parenting, play important roles in nurturing caring personality towards the environment. As a result, residential areas along river banks that were formerly slums become organized and healthy spaces.